Correlates of persisting posttraumatic symptoms in children and adolescents 18 months after a cyclone disaster. (January 2014) - McDermott, Brett; Cobham, Vanessa; Berry, Helen; Kim, Bungnyun
Objective: To describe PTSD symptom persistence and resolution, including the potential phenomenon of late-onset PTSD, in children and adolescents 18 months after a cyclone disaster; and to investigate factors that predict longer-term symptom outcome. Method: 71 children and 191 adolescents who were screened three months after a Category 5 Cyclone were re-screened 18 months post-disaster. Child-report measures included the PTSD Reaction Index, measures of event exposure and social connectedness. Results: Approximately 1-in-5 children and 1-in-12 adolescents endorsed cyclone-related PTSD symptoms at the moderate to severe level 18 months post-disaster. Of these approximately one-half (44.8%) of children were in the 'high-persister' group at 18-month follow-up. Persistence of low symptoms was very common (97.6%) and late-onset PTSD was a rare phenomenon. This pattern was similar in adolescents: 25.0% were in the 'high-persister' group and few students experienced late-onset PTSD. In multivariate analysis, only initial severe to very severe PTSD category made a significant independent contribution to explaining persisting moderate to severe PTSD symptoms in primary school students (ORadj=8.33, 95% CI=1.45-47.84). There was a trend for a similar result in secondary students. Conclusion: A child or adolescent with few PTSD symptoms three months post-disaster is likely to remain so unless a further traumatic event occurs. However, if symptomatic at three months, there is approximately a 30-45% chance that the child or adolescent will still be symptomatic 18 months after the disaster. Given the high rate of students in the 'resolver' group, initial posttraumatic symptoms are a necessary but not sufficient condition for predicting chronic symptomatology. Other targets for predictive modelling include initial threat perception and high and low social connectedness.